Syngonanthus hensoldiae (Eriocaulaceae): another new species of S. sect. Syngonanthus endemic from Chapada dos Veadeiros, Central Brazil - Watanabe, Mauricio Takashi Coutinho; Sano, Paulo Takeo (Phytotaxa, 2016)
We describe and illustrate Syngonanthus hensoldiae, a new species of S. sect. Syngonanthus (Eriocaulaceae) endemic from Chapada dos Veadeiros (Central highlands of Brazil). This region is known for its high number of endemic and threatened species, including other members of Eriocaulaceae family. This new species is known only from small populations on private properties and is considered endangered.